Development of the legal and regulatory framework for the Islamic banking system in Malaysia / Muhamad Rahimi Osman - Osman, Muhamad Rahimi (UPENA, 2006)
The enactment of Islamic Banking Act (IBA) 1983, considered the first Act of Parliament has been legislated specifically to govern Islamic banking business. Following to the introduction of the IBA, the Malaysian government has enacted new laws such as the Government Investment Act (GIA) and Takaful Act. It also resulted in the amendment of the existing laws such as Banking and Financial Institutions Act (BAFIA), Central Bank of Malaysia Act, Stamp Act, etc. The purpose of this paper is to examine the development of the legal framework for the Malaysian Islamic banking system. In doing so, this paper analyses the statutes which govern Islamic banking system. These statutes could be divided into two parts; firstly the statutes which enacted to govern Islamic banks and secondly the existing statutes which have been amended to accommodate and to facilitate the practice of the Islamic banking system. Since the Shari 'ah Advisory Council plays a crucial role to ensure the Islamic banks comply strictly with the Shari 'ah principles, the final part of this paper will also examines the status and function of the SAC in the Islamic banking industry.